1992
DOI: 10.1080/00207599208246873
|View full text |Cite
|
Sign up to set email alerts
|

Roles, Responsibility, and Accounts Across Cultures

Abstract: In research on the attribution of responsibility, increasing attention is being paid to the fact that responsibility judgments are social negotiations, not just the cognitions of isolated individuals. In this negotiating process, accow~cs, including excuses and justifications, may diminish or even eliminate responsibility for wrongdoing. This paper presents a perspective on responsibility attribution and reviews recent literature on accounts. It emphasizes the way in which aspects of social roles-specifically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 19 publications
2
70
0
1
Order By: Relevance
“…The 12th century philosopher, Anselm de Canterbury discussed injustice as a state of mind that demanded retribution; where injustice could only be resolved when the order of retribution was equal to that of experienced loss [45]. Issues related to the defining features of justice have been debated in philosophy, and mechanisms for the resolve of injustice are represented at varying levels of social policy [12,46]. In many industrialized societies, 'retribution' for losses incurred due to injury has taken the form of compensation or litigation [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 12th century philosopher, Anselm de Canterbury discussed injustice as a state of mind that demanded retribution; where injustice could only be resolved when the order of retribution was equal to that of experienced loss [45]. Issues related to the defining features of justice have been debated in philosophy, and mechanisms for the resolve of injustice are represented at varying levels of social policy [12,46]. In many industrialized societies, 'retribution' for losses incurred due to injury has taken the form of compensation or litigation [17].…”
Section: Discussionmentioning
confidence: 99%
“…Perceptions of injustice can ensue from acts or conditions that might cause someone to suffer hardship or loss undeservedly [12,13]. Research has shown that perceptions of injustice are likely to arise when an individual is exposed to situations that are characterized by a violation of basic human rights, transgression of status or rank, or challenge to equity norms and just world beliefs [14][15][16].…”
mentioning
confidence: 99%
“…Perceptions of injustice can arise under conditions where someone suffers hardship or loss undeservedly (Hamilton and Hagiwara 1992;Lind and Tyler 1988). Research has shown that perceptions of injustice are likely to arise when an individual is exposed to situations that are characterized by a violation of basic human rights, transgression of status or rank, or challenge to equity norms and just world beliefs (Fetchenhauer and Huang 2004;Hafer and Begue 2005;Mohiyeddini and Schmitt 1997).…”
Section: Introductionmentioning
confidence: 97%
“…Since Joan Miller (1984) first demonstrated the importance of culture in causal attribution, numerous studies within diverse attributional domains and using different methodologies have been conducted to examine culture variations and universality in the causal attribution process (e.g., Choi, Nisbett, & Norenzayan, 1999;Carpenter, 2000;Kivilu & Rogers, 1998;Norenzayan, Choi, & Nisbett, 2002), and regarding the theme of responsibility (e.g., Hamilton & Hagiwara, 1992;Zhang, Guan, Zhou, & Lu, 2003). The present research attempted to explore if Weiner's theory is a general, pan-cultural model which fits teachers who belong to different cultures and work in different school systems or if it is a theory which reflects a culturally-specific sociocognitive process (Duda & Allison, 1989).…”
Section: Second Part -Experimentsmentioning
confidence: 99%